2022
DOI: 10.2807/1560-7917.es.2022.27.1.2101110
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine effectiveness against severe acute respiratory infections (SARI) COVID-19 hospitalisations estimated from real-world surveillance data, Slovenia, October 2021

Abstract: We estimated vaccine effectiveness (VE) against severe COVID-19 during October 2021, using Slovenian surveillance data. For people fully vaccinated with any vaccine in age groups 18–49, 50–64, ≥ 65 years, VE was 86% (95% CI: 79–90), 89% (85–91), and 77% (74–81). Among ≥ 65 year-olds fully vaccinated with mRNA vaccines, VE decreased from 93% (95% CI: 88–96) in those vaccinated ≤ 3 months ago to 43% (95% CI: 30–54) in those vaccinated ≥ 6 months ago, suggesting the need for early boosters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…It should be noted that for both groups, those who received two and those who received three doses, such high VE lasted for at least 6 months after the last dose received. This was unlike the SARI COVID-19 waning immunity we observed during the period of Delta predominance, in a previous VE study using the same methodology and data sources [ 1 ]. Understanding how much longer the high protection against Omicron-related SARI COVID-19 hospitalisation will last, will only be possible in the future, when the number of people vaccinated with the third dose more than 6 months ago will accumulate.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…It should be noted that for both groups, those who received two and those who received three doses, such high VE lasted for at least 6 months after the last dose received. This was unlike the SARI COVID-19 waning immunity we observed during the period of Delta predominance, in a previous VE study using the same methodology and data sources [ 1 ]. Understanding how much longer the high protection against Omicron-related SARI COVID-19 hospitalisation will last, will only be possible in the future, when the number of people vaccinated with the third dose more than 6 months ago will accumulate.…”
Section: Discussioncontrasting
confidence: 65%
“…Surveillance of SARI COVID-19 cases within EPISARI has some limitations, which have been described in detail previously [ 1 , 3 ]. However, it is rather unlikely that SARI COVID-19 cases admissions to hospitals, the outcome used in the analysis, would not be ascertained correctly in most cases and reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory symptoms of COVID-19 infection can be various, such as cough, shortness of breath and dyspnea [ 4 ]. Numerous studies have demonstrated the effectiveness of COVID-19 vaccination in mitigating severe symptoms, hospitalization resulting from COVID-19 infection, mortality and long-COVID symptoms, including respiratory symptoms and headaches in the general population [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. According to a study by Taylor et al Vaccines against COVID-19 could both prevent and help in treating long COVID [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, real-world comprehensive SARI surveillance is of uttermost importance in the light of the ongoing pandemic and is established in several European countries including Germany. [13][14][15][16] Routine data fully based on ICD-codes should be considered a reliable data source to serve this purpose as has also been stated by authors of a previous study focusing on emergency department attendees in Germany. 17 Monitoring timely trends of COVID-19 and SARI cases can also facilitate the assessment of SARS-CoV-2-related disease severity, which was just recently proposed by members of this author group.…”
mentioning
confidence: 99%